Clinical Outcomes, Tendon Integrity, and Shoulder Strength After Revision Rotator Cuff Reconstruction: A Minimum 2 Years' Follow-up. Issue 11 (September 2018) - Willinger, Lukas; Lacheta, Lucca; Beitzel, Knut; Buchmann, Stefan; Woertler, Klaus; Imhoff, Andreas B.; Scheiderer, Bastian
Background: The retear rate after primary rotator cuff (RC) reconstruction is high and commonly leads to poorer clinical outcomes and shoulder function. In the case of primary failure, revision RC reconstruction (RCR) has become increasingly important to re-create RC integrity and improve outcomes. To date, clinical and structural outcomes after RCR have not been sufficiently investigated and described at midterm follow-up. Hypothesis/Purpose: The purpose was to evaluate the clinical and radiological outcomes after revision RCR. It was hypothesized that revision RCR significantly improves clinical outcomes and that the outcomes positively correlate with tendon integrity on magnetic resonance imaging (MRI). Study Design: Case series; Level of evidence, 4. Methods: Patients who underwent revision RCR between 2008 and 2014 were retrospectively evaluated with a minimum follow-up of 2 years. Outcomes were assessed by a clinical examination, a visual analog scale for pain (VAS), the Constant Score (CS), the American Shoulder and Elbow Surgeons (ASES) score, and the Disabilities of the Arm, Shoulder and Hand (DASH) score. Tendon integrity was determined using 3-T MRI and graded according to the Sugaya classification. Results: Thirty-one of 40 patients (77.5%) were available for the final assessment at a mean follow-up of 50.3 ± 20.4 months. Clinical outcome scores significantly improved from preoperatively to postoperatively for the CS (39.7 ± 16.7 to 65.1 ± 19.7; P < .001), ASES (44.2 ± 17.7 to 75.2 ± 24.8; P < .001), and DASH (68.6 ± 15.1 to 21.5 ± 19.1; P < .001). The VAS score decreased from 6.1 ± 1.8 preoperatively to 1.3 ± 1.8 at final follow-up ( P < .001). MRI demonstrated a retear rate of 55.5%. No differences in CS, ASES, and DASH scores were detected between patients with an intact repair and failure. Abduction strength was not significantly different in patients with an intact repair and retears (55.5 N vs 44.0 N, respectively, P = .52). Conclusion: Revision RCR improves clinical outcomes and shoulder function at midterm follow-up. The clinical outcome scores were comparable in patients with an intact repair and those with failed RC healing. Therefore, tendon integrity was not correlated with better clinical outcomes after revision RCR at final follow-up.